2014
DOI: 10.1021/tx500159w
|View full text |Cite
|
Sign up to set email alerts
|

Major Groove Orientation of the (2S)-N6-(2-Hydroxy-3-buten-1-yl)-2′-deoxyadenosine DNA Adduct Induced by 1,2-Epoxy-3-butene

Abstract: 1,3-Butadiene (BD) is an environmental and occupational toxicant classified as a human carcinogen. It is oxidized by cytochrome P450 monooxygenases to 1,2-epoxy-3-butene (EB), which alkylates DNA. BD exposures lead to large numbers of mutations at A:T base pairs even though alkylation of guanines is more prevalent, suggesting that one or more adenine adducts of BD play a role in BD-mediated genotoxicity. However, the etiology of BD-mediated genotoxicity at adenine remains poorly understood. EB alkylates the N6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Structural studies of (S) - N 6 -HB-dA I in 5′-d(C 1 G 2 G 3 A 4 C 5 Y 6 A 7 G 8 A 9 A 10 G 11 )-3′:5′-d(C 12 T 13 T 14 C 15 T 16 T 17 G 18 T 19 C 20 C 21 C 22 )-3′ using high field NMR ( Y 6 = (S) - N 6 -HB-dA I) 60 have revealed that the adduct is accommodated in the major grove of the DNA, maintaining standard Watson-Crick base pairing with T 17 . 60 Although (S) - N 6 -HB-dA I ( Y 6 ) did not stack well with its 5′ neighbor (C 5 ), it stacked normally with its 3′ neighbor (A 7 ), thereby leading to only minor perturbations in the overall DNA structure. Structurally analogous N 6 -THB-dA and N 6 -dA adducts are also readily accommodated in the DNA major grove, maintaining Watson-Crick base pairing.…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies of (S) - N 6 -HB-dA I in 5′-d(C 1 G 2 G 3 A 4 C 5 Y 6 A 7 G 8 A 9 A 10 G 11 )-3′:5′-d(C 12 T 13 T 14 C 15 T 16 T 17 G 18 T 19 C 20 C 21 C 22 )-3′ using high field NMR ( Y 6 = (S) - N 6 -HB-dA I) 60 have revealed that the adduct is accommodated in the major grove of the DNA, maintaining standard Watson-Crick base pairing with T 17 . 60 Although (S) - N 6 -HB-dA I ( Y 6 ) did not stack well with its 5′ neighbor (C 5 ), it stacked normally with its 3′ neighbor (A 7 ), thereby leading to only minor perturbations in the overall DNA structure. Structurally analogous N 6 -THB-dA and N 6 -dA adducts are also readily accommodated in the DNA major grove, maintaining Watson-Crick base pairing.…”
Section: Discussionmentioning
confidence: 99%
“…The overall B-DNA structure was maintained. 65,66 Strand incision assays conducted with site-specifically modified DNA duplexes and nuclear extracts from human fibrosarcoma (HT1080) cells (Figures 2 and 3) suggest that all three BD-dA adducts are efficiently recognized and processed by a BER pathway. In these experiments, 5′-radiolabeled DNA duplexes containing site-specific and stereospecific BD-dA adducts were incubated with nuclear protein extracts, and the cleavage products were detected as high-mobility bands on the gel.…”
Section: ■ Discussionmentioning
confidence: 97%
“…Only small perturbations in base stacking and hydrogen bonding interactions were observed for ( S )- N 6 -HB-dA, while the presence of N 6 , N 6 -DHB-dA prevented its hydrogen bonding with thymidine in the opposite strand and disrupted stacking interactions of the adducted base with neighboring nucleotides. The overall B-DNA structure was maintained. , …”
Section: Discussionmentioning
confidence: 99%
“…The formation of CBO-dA adducts will disrupt Watson–Crick base paring, thus being likely mutagenic. Indeed, multiple studies have showed that the N 6 -dA adducts in DNA can disrupt Watson–Crick base pairing, potentially inducing mutations . Recently, it has been demonstrated that N 6 -singly substituted dA lesions are not miscoding but that exocyclic N 6 , N 6 -dA adducts are strongly mispairing, probably due to their inability to form stable Watson–Crick pairs with dT .…”
Section: Discussionmentioning
confidence: 99%